DECISION-MAKING MODEL IN SELECTING STRATEGY FOR FOOD SUPPLY IN LIVESTOCK BUSINESS USING ANALYTICAL HIERARCHY PROCESS (AHP) - Agustine Hernowo, Ayu
In the beef cattle business, there are essential components that support the success of the business. The factors that influence the success of beef cattle farming include business experience, business capital, number of livestock, number of workers, management education, feed, and medicines. From the factors mentioned above, it is known that the feed is one of the success factor and it is contributed 50.20% of the total cost. Based on the number of feed cost contribution of the total cost in the livestock business, the internal management should find the most effective and efficient feed supply to be applied. Based on Stevenson 2005 it is known that the supply strategy consist of two, which are outsource and insource. In this study an analysis will be carried out to consider whether the outsource or insource method is more profitable for the company as a future strategy for fulfilling the feed.